Nilai dan Fungsi Kesenian Kothekan Lesung di desa Wisata Pandean Kabupaten Trenggalek - Mustika Maulany Sabilla Putri; I Nengah Mariasa; Setyo Yanuartuti (Program Studi Pendidikan Musik FBS UNP, 2023)
Purpose: This research aims to describe the value and function of the Shotokan dimple art in Pandean Tourism Village. This research is expected to serve as a basis for further investigation. Method: The research approach used is qualitative research. Data collection techniques were obtained from interviews, literature and documentation. Result and Discussion: The results of this study indicate that the values contained in the mortar kothekan include cooperation, discipline, hard work, tolerance and others. The Pandean Tourism Village and the Tourism Awareness Group (POKDARWIS) are collaborating with traditional arts in the Tourism Village program to preserve traditional skills and maintain their character values. Kothekan mortar, initially used by farmers as entertainment to relieve fatigue, now has several other functions. The involvement of the kothekan lesung art in the Tourism Village gives this art have 3 (three) artistic functions, namely: 1) personal function, 2) social function, and 3) physical function.